ANALISIS YURIDIS PERTIMBANGAN HUKUM HAKIM TERHADAP PELANGGARAN HAK CIPTA LAGU (PUTUSAN MAHKAMAH AGUNG NOMOR 41 PK/Pdt.Sus-HKI/2021) - NIM. A1011221208, DIAN AYU LESTARI BAHARI (Jurnal Fatwa Hukum, 2025)
Abstract The development of digital Platforms expands the use of copyrighted works, including songs, while increasing the potential for copyright infringement such as unauthorized use, lyric alteration, and commercialization by other parties. This action is contrary to Law Number 28 of 2014 which guarantees the moral and economic rights of creators. Based on these conditions, this study examines the legal competition of judges in the case of song copyright infringement in the Supreme Court Decision Number 41 PK/Pdt.Sus-HKI/2021. This study uses normative research methods with a legislative, case-based, conceptual, and comparative approach. With the nature of descriptive research analysis. The data used are secondary data in the form of primary legal materials such as laws and court decisions, as well as secondary legal materials in the form of legal literature, journals, and expert views. Data collection techniques with literature studies and document studies. The analysis is carried out qualitatively through legal interpretation and argumentative construction based on the principles of civil law and copyright provisions. With this method, the research is directed to systematically understand the judge's legal considerations as well as the civil consequences arising from song copyright infringement. The results of the study show that the Supreme Court considered the previous ruling to be wrong in applying the law, especially regarding the violation of the moral rights and economic rights of creators. Altering lyrics, duplication, and using works without permission is proven to meet the elements of infringement according to the Copyright Law, so the determination of compensation has a strong legal basis. In addition, the consequences of civil law in the form of the obligation to pay compensation of Rp300,000,000 based on the principle of ex aequo et bono affirm the existence of financial responsibility and the restoration of copyright rights. This study confirms that copyright infringement not only harms moral rights and economic rights, but also poses concrete civil law consequences. Keywords: Copyright, Indemnity, Music, Song, Infringement. Abstract Perkembangan Platform digital memperluas pemanfaatan karya cipta, termasuk lagu, sekaligus meningkatkan potensi pelanggaran hak cipta seperti penggunaan tanpa izin, pengubahan lirik, dan komersialisasi oleh pihak lain. Tindakan tersebut bertentangan dengan Undang-Undang Nomor 28 Tahun 2014 yang menjamin hak moral dan hak ekonomi pencipta. Berdasarkan kondisi tersebut, penelitian ini mengkaji pertembingan hukum hakim dalam perkara pelanggaran hak cipta lagu pada Putusan Mahkamah Agung Nomor 41 PK/Pdt.Sus-HKI/2021. Penelitian ini menggunakan metode penelitian normatif dengan pendekatan perundang-undangan, pendekatan kasus, pendekatan konseptual, dan komparatif. Dengan sifat penelitian deskriptif analisis. Data yang digunakan adalah data sekunder berupa bahan hukum primer seperti undang-undang dan putusan pengadilan, serta bahan hukum sekunder berupa literatur hukum, jurnal, dan pandangan ahli. Teknik pengumpulan data dengan studi kepustakaan dan studi dokumen. Analisis dilakukan secara kualitatif melalui penafsiran hukum dan konstruksi argumentasi berdasarkan asas-asas hukum perdata dan ketentuan hak cipta. Dengan metode ini, penelitian diarahkan untuk memahami secara sistematis pertimbangan hukum hakim serta konsekuensi perdata yang muncul dari pelanggaran hak cipta lagu. Hasil penelitian menunjukkan bahwa Mahkamah Agung menilai putusan sebelumnya keliru dalam menerapkan hukum, khususnya terkait pelanggaran hak moral dan hak ekonomi pencipta. Pengubahan lirik, penggandaan, dan penggunaan karya tanpa izin terbukti memenuhi unsur pelanggaran menurut Undang-Undang Hak Cipta, sehingga penetapan ganti rugi memiliki dasar hukum yang kuat. Selain itu, akibat hukum perdata berupa kewajiban membayar ganti rugi sebesar Rp300.000.000 berdasarkan asas ex aequo et bono menegaskan adanya tanggung jawab finansial dan pemulihan hak pencipta. Penelitian ini menegaskan bahwa pelanggaran hak cipta tidak hanya merugikan hak moral dan hak ekonomi, tetapi juga menimbulkan konsekuensi hukum perdata yang konkret. Kata Kunci: Hak Cipta, Ganti Rugi, Musik, Lagu, Pelanggaran.